Political violence in ancient India - Singh, Upinder (Cambridge, Massachusetts ; London, England : Harvard University Press, 2017)
Political Violence in Ancient India argues that the idea of a nonviolent India is an artificial twentieth-century construct deeply influenced by Gandhi and Nehru. Ancient Indian history is marked by considerable violence of various kinds, as is the history of other parts of the world. However the issue of violence was debated in India with greater intensity than elsewhere. There was a recognition of the possibility of necessary force veering into violence, and of the strong tension between violence and nonviolence in the political sphere. This book looks at the evolution of the theory and practice of kingship and the attitudes towards political violence between c. 600 BCE and 600 CE by examining a vast array of texts, inscriptions, artistic representations, and numismatic and archaeological material. These include the ideas of Buddhism and Jainism; the emperor Ashoka; the Sanskrit epics, the Ramayana and Mahabharata; the political treatise, the Arthashastra; and the poetry of Kalidasa. The book examines how the problem of the relationship between kingship and violence was addressed in general as well with reference to punishment, war and the forest.--
Foundation -- Transition -- Maturity -- War -- The wilderness.
Includes bibliographical references (pages 555-584) and index.
Keywords: Political violence -- India -- History; Violence -- Moral and ethical aspects -- India; Nonviolence -- Political aspects -- India -- History; Violence in popular culture -- India -- History; India -- History -- To 324 B.C.; India -- History -- 324 B.C.-1000 A.D.; India -- Politics and government -- To 997.